Biomimetic Microfingerprints for Anti‐Counterfeiting Strategies. (6th February 2015) - Bae, Hyung Jong; Bae, Sangwook; Park, Cheolheon; Han, Sangkwon; Kim, Junhoi; Kim, Lily Nari; Kim, Kibeom; Song, Suk‐Heung; Park, Wook; Kwon, Sunghoon
Abstract : An unclonable, fingerprint‐mimicking anti‐counterfeiting strategy is presented that encrypts polymeric particles with randomly generated silica film wrinkles. The generated wrinkle codes are as highly unique as human fingerprints and are technically irreproducible. Superior to previous physical unclonable functions, codes are tunable on demand and generable on various geometries. Reliable authentication of real‐world products that have these microfingerprints is demonstrated using optical decoding methods.